Generalidades de Enfermedad Celiaca y abordaje diagnóstico - Murillo Saviano, José Alfredo (2019)
The celiac disease (CD) is a permanent Gluten intolerance, with a prevalence of 1%, which increases in people with autoimmune diseases, chromosomopathies, or first degree relatives with CD. Clinically it can be asymptomatic, or produce a florid malabsorption syndrome, with gastrointestinal and extra gastrointestinal symptoms, with impaired nutritional status. The diagnosis is made based on clinical suspicion, serological tests, genetic studies (HLA DQ2 / 8), and the duodenal biopsy, that is the gold standard for diagnosis. The treatment is maintaining a gluten-free diet for life.